An update on pulmonary rehabilitation techniques for patients with chronic obstructive pulmonary disease. (1st February 2020) - Wouters, Emiel FM; Posthuma, Rein; Koopman, Maud; Liu, Wai-Yan; Sillen, Maurice J; Hajian, Bita; Sastry, Manu; A. Spruit, Martijn; Franssen, Frits M.
ABSTRACT: Introduction : Pulmonary rehabilitation (PR) is one of the core components in the management of patients with chronic obstructive pulmonary disease (COPD). In order to achieve the maximal level of independence, autonomy, and functioning of the patient, targeted therapies and interventions based on the identification of physical, emotional and social traits need to be provided by a dedicated, interdisciplinary PR team. Areas covered : The review discusses cardiopulmonary exercise testing in the selection of different modes of training modalities. Neuromuscular electrical stimulation as well as gait assessment and training are discussed as well as add-on therapies as oxygen, noninvasive ventilator support or endoscopic lung volume reduction in selected patients. The potentials of pulsed inhaled nitric oxide in patients with underlying pulmonary hypertension is explored as well as nutritional support. The impact of sleep quality on outcomes of PR is reviewed. Expert opinion : Individualized, comprehensive intervention based on thorough assessment of physical, emotional, and social traits in COPD patients forms a continuous challenge for health-care professionals and PR organizations in order to dynamically implement and adapt these strategies based on dynamic, more optimal understanding of underlying pathophysiological mechanisms.